Research on the Vibration Insulation of High-Speed Train Bogies in Mid and High Frequency - Jia Liu; Xuesong Jin (Shock and Vibration)
According to a large amount of the test data, the mid and high frequency vibrations of high-speed bogies are very notable, especially in the 565~616 Hz range, which are just the passing frequencies corresponding to the 22nd to 24th polygonal wear of the wheel. In order to investigate the main cause of wheel higher-order polygon formation, a 3D flexible model of a Chinese high-speed train bogie is developed using the explicit finite element method. The results show that the couple vibration of bogie and wheelset may lead to the high-order wears of wheel. In order to reduce the coupled resonance of the wheelset and the bogie frame, the effects of the stiffness and damping of the primary suspensions, wheelset axle radius, and bogie frame strength on the vibration transmissibility are discussed carefully. The numerical results show that the resonance peaks in high frequency range can be reduced by reducing the stiffness of axle box rotary arm joint, reducing the wheelset axle radius or strengthening the bogie frame location. The related results may provide a reference for structure improvement of the existing bogies and structure design of the new high-speed bogies.